Long‐Life Room‐Temperature Sodium–Sulfur Batteries by Virtue of Transition‐Metal‐Nanocluster–Sulfur Interactions. Issue 5 (2nd January 2019) - Zhang, Bin‐Wei; Sheng, Tian; Wang, Yun‐Xiao; Chou, Shulei; Davey, Kenneth; Dou, Shi‐Xue; Qiao, Shi‐Zhang
Abstract: Room‐temperature sodium–sulfur (RT‐Na/S) batteries hold significant promise for large‐scale application because of low cost of both sodium and sulfur. However, the dissolution of polysulfides into the electrolyte limits practical application. Now, the design and testing of a new class of sulfur hosts as transition‐metal (Fe, Cu, and Ni) nanoclusters (ca. 1.2 nm) wreathed on hollow carbon nanospheres (S@M‐HC) for RT‐Na/S batteries is reported. A chemical couple between the metal nanoclusters and sulfur is hypothesized to assist in immobilization of sulfur and to enhance conductivity and activity. S@Fe‐HC exhibited an unprecedented reversible capacity of 394 mAh g −1 despite 1000 cycles at 100 mA g −1, together with a rate capability of 220 mAh g −1 at a high current density of 5 A g −1 . DFT calculations underscore that these metal nanoclusters serve as electrocatalysts to rapidly reduce Na2 S4 into short‐chain sulfides and thereby obviate the shuttle effect. Abstract : Enhancing sulfur : Transition‐metal nanoclusters (ca. 1.2 nm) wreathed on hollow carbon nanospheres as S hosts were applied to enhance conductivity and activity of sulfur. These nanoclusters chemisorb the resultant polysulfide and electrocatalyze these into short‐chain sulfides, thus achieving excellent cycling stability and rate performance for room‐temperature sodium–sulfur batteries.